The Synthesis of Alginate-Capped Silver Nanoparticles under Microwave Irradiation - Foliatini, Foliatini; Yulizar, Yoki; Hafizah, Mas Ayu Elita (Journal of Mathematical and Fundamental Sciences, 2015)
Synthesis of silver nanoparticles (Ag-NP) was successfully performed within a few minutes by microwave irradiation of the precursor salt (AgNO3) and alginate mixed solution in one pot. Herein, alginate molecules acted as both a reducing and stabilizing agent for the preparation of the silver nanoparticles. The obtained nanoparticles were characterized by ultraviolet-visible (UV-Vis) spectroscopy, particle size analysis (PSA), Fourier transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM). The pH and concentration ratio of the alginate/metal precursor salt greatly influenced the particle size and its distribution of Ag-NP. The higher the pH the higher the nucleation rate and the larger the electrostatic stabilization, while both of them were responsible for producing a smaller particle size and a narrower size distribution. A higher concentration ratio also yielded a smaller particle size and a narrower size distribution, but above the optimum ratio, the trend was conversely changed due to the reducing capability of the alginate, which was dominant above the optimum ratio, thus creating a high density of nuclei, allowing aggregation to occur. A lower ratio not only led to a higher tendency to produce larger particles, but also a higher probability of anisotropic particle shape formation due to the lack of reducing capability of the alginates.